Techno-economic optimization of battery storage technologies for off-grid hybrid microgrids in multiple rural locations of Bangladesh - Ali, Md. Feroz; Biswas, Diganto; Sheikh, Md. Rafiqul Islam; Al Mamun, Abdullah; Hossen, Md. Jakir (Frontiers in Energy Research, 2025)
Rural communities in Bangladesh face persistent energy access challenges due to geographic isolation and inadequate infrastructure. This study investigates the design and optimization of off-grid hybrid renewable energy systems for five distinct rural locations, utilizing solar photovoltaic (PV), wind turbines (WT), and four types of battery energy storage systems (BESS): ZnBr Flow, Li-Ion NMC, Lead-Acid, and LiFePO4. Using HOMER Pro (version 3.14.2), simulations were performed based on real hourly load profiles and resource data (solar irradiance, wind speed, and temperature) from NASA. Each system configuration was assessed for economic feasibility, renewable energy penetration, and environmental impact. Results show that the PV-WT-ZnBr Flow battery configuration outperformed others at all sites, achieving the lowest Net Present Cost (NPC) of 171,720, Cost of Energy (COE) of 0.0688/kWh, and 100% Renewable Fraction (RF) with zero carbon emissions. ZnBr Flow batteries demonstrated high efficiency, long lifespan (30 years), and low maintenance requirements. Sensitivity analysis revealed the influence of resource variability, load profiles, and component costs. This study confirms that ZnBr-based hybrid microgrids offer a viable, cost-effective, and scalable solution for sustainable rural electrification in Bangladesh and other remote or underdeveloped regions worldwide.